ANALYSIS OF WAQF LAND LEASES IN THE PERSPECTIVE OF THE SYAFI’IYYAH MAZDHAB PADA MASJID NURUL HUDA DUSUN KEDUNGREJO DESA SAMBIMULYO KECAMATAN BANGOREJO KABUPATEN BANYUWANGI - Yunus Zamroji (Jurnal Ekonomi Syariah Darussalam, 2023)
The purpose of this study is to analyze the nazdir law of leasing waqf land for the Nurul Huda Mosque in Kedungrejo Hamlet, Sambimulyo Village, Bangorejo District, Banyuwangi Regency based on the opinion of the Syafi’i School. This research method is field research with a qualitative approach to produce descriptive data in the form of observed words and behavior. In the data analysis process, there are three components, namely data reduction, data presentation, drawing conclusions and verifying conclusions. The conclusion drawn from these results is that the waqf land leased by the Nurul Huda Mosque in Kedungrejo Hamlet, Sambimulyo Village, Bangorejo District, Banyuwangi Regency was carried out by the waqf nazir based on the results of the deliberations attended by the waqf nazir, mosque administrators, community leaders and mosque youth in accordance with sharia provisions, this is based on several reasons; nazir in leasing this is based on the concepts of hajat, mashlahah and ghibthab, the wakif party at the time of endowment never requires it not to be rented out and when the wakif donates the land, the 'urf that applies is that the waqf land of the mosque is leased